2017
DOI: 10.1002/2017ef000642
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Dynamical Downscaling Ensemble Projections of Future Extreme Temperature Distributions for the United States

Abstract: The aim of this study is to examine projections of extreme temperatures over the continental United States (CONUS) for the 21st century using an ensemble of high spatial resolution dynamically downscaled model simulations with different boundary conditions. The downscaling uses the Weather Research and Forecast model at a spatial resolution of 12 km along with outputs from three different Coupled Model Intercomparison Project Phase 5 global climate models that provide boundary conditions under two different fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…The primary objective of this research is to better understand precipitation extremes using high-spatial-resolution climate models and to provide regional information about the potential hydrology and agriculture impacts of climate. Our precipitation data continue the analysis of historical biases that Zobel et al (2017Zobel et al ( , 2018 began; the Zobel et al (2017Zobel et al ( , 2018 studies quantified future uncertainties associated with temperature extremes in the United States. The initial objective of our study is to quantify the added value-or lack thereof-dynamical downscaling has over its ESM counterpart for both extreme events and seasonal mean precipitation (section 3.1).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The primary objective of this research is to better understand precipitation extremes using high-spatial-resolution climate models and to provide regional information about the potential hydrology and agriculture impacts of climate. Our precipitation data continue the analysis of historical biases that Zobel et al (2017Zobel et al ( , 2018 began; the Zobel et al (2017Zobel et al ( , 2018 studies quantified future uncertainties associated with temperature extremes in the United States. The initial objective of our study is to quantify the added value-or lack thereof-dynamical downscaling has over its ESM counterpart for both extreme events and seasonal mean precipitation (section 3.1).…”
Section: Introductionmentioning
confidence: 73%
“…These results are also supported by Cook et al (2008), who found that increasing LLJ strength peaks earlier in the year for future simulations. The large increase in springtime Midwest precipitation is also likely the primary driver for the Midwest experiencing the smallest regional shift in the extreme June-July-August temperature presented in Zobel et al (2017). Changing atmospheric dynamics in a warmer climate likely played a more significant role in Midwestern intensity changes than increasing surface temperatures and led to the peak precipitation intensity occurring at lower temperatures in future simulations.…”
Section: 1029/2018ef000956mentioning
confidence: 97%
See 1 more Smart Citation
“…The coupled land-lake-atmospheric interactions will help to capture impacts of changing land cover, precipitation, and the timing and intensity of runoff, which influence the biogeochemistry of streams and rivers. Future increase in intensity of extreme summer storms (Kunkel et al, 1999;Zobel et al, 2017) and biogeochemical cycles are closely tied to hydrological response, both as a mechanism for solute transport (e.g., Royer et al, 2004Royer et al, , 2006 and as a driver of redox potential in soils (Christopher et al, 2008). Thus, agriculture intensification via an increase in fertilizer consumption would cause more problems…”
Section: Agricultural Impactsmentioning
confidence: 99%
“…Global climate change has already begun to modify both the regional climate and the physical behavior of the Great Lakes (Kling et al, ; Lofgren et al, ; Wuebbles et al, ; Wuebbles & Hayhoe, ), while intensifying regional hydrometeorological and thermal extremes (Winkler et al, ). In recent decades a panoply of such changes have been documented: a statistically significant warming trend (Schoof, ; Zobel et al, , ), an increase in extreme summertime precipitation (Kunkel et al, , ), extreme changes in lake levels (Gronewold et al, ), and a reversal of the increasing trends in lake‐effect snows (Bard & Kristovich, ; Clark et al, ; Kunkel et al, ; Norton & Bolsenga, ; Notaro et al, ; Suriano & Leathers, ). More recently, the region has also seen changes in the quantity and timing of extreme precipitation and runoff, which have important implications for flooding, soil erosion, nutrient export, and agricultural best management practices (Carpenter et al, ; Kelly et al, ).…”
Section: Introductionmentioning
confidence: 99%